TRANSPARANSI DAN AKUNTABILITAS MANAJEMEN PEMBIAYAAN PENDIDIKAN ISLAM: KAJIAN KONSEPTUAL - Saefuddaulah Mehir; Toto Sukarnoto; Feri Herdiana (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Islamic education financing management holds a strategic position in establishing institutional accountability and public trust. This study aims to examine the conceptual dimensions of transparency and accountability in Islamic education financing management through an in-depth literature review approach. The methodology employed is a qualitative library research method by systematically analyzing primary and secondary sources consisting of books, scientific journals, and relevant policy documents. The results of this study indicate that transparency and accountability in Islamic education financing are not merely technical administrative obligations, but are deeply rooted in the principles of Islamic governance (Islamic governance values), namely amanah (trustworthiness), adl (justice), and masuliyyah (responsibility). The study further reveals that the integration of a sound financial governance framework, robust internal control mechanisms, and a participatory culture among educational stakeholders significantly reinforces the quality of financial reporting and the credibility of Islamic educational institutions. The conceptual gap identified in this study pertains to the absence of a comprehensive and integrative model that holistically bridges the Islamic normative values with modern financial management practices in the context of Islamic educational institutions.